Consensus standards for introductory e-learning courses in human participants research ethics - Williams, R. (Journal of medical ethics, 2014)
This paper reports the results of a workshop held in January 2013 to begin the process of establishing standards for e-learning programmes in the ethics of research involving human participants that could serve as the basis of their evaluation by individuals and groups who want to use, recommend or accredit such programmes. The standards that were drafted at the workshop cover the following topics: designer/provider qualifications, learning goals, learning objectives, content, methods, assessment of participants and assessment of the course. The authors invite comments on the draft standards and eventual endorsement of a final version by all stakeholders.